Транспортно-логістична складова стратегій поводження з відходами в контексті реалізації ресурсозберігаючої та природоохоронної політики - Kodzhebash, Alina; Krivencev, Alexander (Dr. Viktor Koval, 2018)
Introduction. The overall situation in the field of waste management in Ukraine is extremely difficult, which is explained by the lack of preventive resource conservation and environmental protection policies, as well as the lack of financing of measures aimed at eliminating the negative consequences resulting from the increasing generation of waste. In particular, due to insufficient financing of landfill contents: there are violations of the schedules of their sanitary cleaning, which leads to the formation of spontaneous landfills in the territories of residential development, especially in rural areas; there are cases of chaotic accumulation of waste that is not compacted and not filled with soil; most landfills and the surrounding area have a terrible look. The general state of waste in Ukraine highlights the urgency and seriousness  of the problem of domestic and industrial waste management. Aim and tasks. The purpose of the article is to substantiate the role and disclosure of the peculiarities of the transport and logistics component of waste management strategies in the context of implementing resource-saving and environmental policy in Ukraine. Results. As a result of the research it is determined that the reform of the waste management system is necessary, which envisages solving of such key organizational, economic and managerial tasks in the context of realization of resource saving and environmental protection policy in Ukraine. The organizational and economic directions of waste management reform are: effective implementation of separate waste collection; construction of new landfills and waste treatment plants; information and institutional support for issues related to waste management; economically justified tariff formation ; stabilization of the finance industry through the introduction of a system of fines for violating legislation, in particular, on the separate collection of waste and the transfer of funds received to the development of the industry, investments provided by state guarantees on the return of capital invested by the investor. Conclusions. At present the reform of the waste management system is necessary by means of solving a series of interrelated organizational, economic and managerial tasks in the context of implementation of resource conservation and environmental protection policy in Ukraine. In particular, it is about the need for financial stabilization of the industry, the expediency of strengthening regulatory instruments and, at the same time, motivational instruments, etc. Based on the analysis of the relationship between these objectives and the objectives of environmental policy, in particular in the field of transport and logistics, as well as the content and constituents of waste management strategies in Ukraine, it was concluded that there is a need for an integrated approach to determine the role and place of transport-logistic component.